Antimicrobial Activity of Glass Ionomer Cements with Chlorhexidine and Propolis: An In Vitro Study - Tuncdemir, Makbule Tugba; Ugur, Ayşe Ruveyda; Ozdemir, Bilgen (Journal of Pediatric Infectious Diseases, 2019)
The aim of this study was to evaluate the antibacterial effect of conventional glass ionomer cement with the addition of antibacterial constituents in its liquid preparation. Two groups of glass ionomers prepared with propolis and chlorhexidine and a third group without any additive used as control were sterilized by low-temperature hydrogen peroxide plasma sterilizer at the sterilization unit. Seven to eight disk-shaped restorative materials of each group were placed on the Mueller Hinton Agar with sheep blood 5% v/v, on which Streptococcus mutans inoculated. The plates were incubated at 37°C in 5% CO2 for 24 to 48 hours. After 24-hour and 48-hour-incubation, inhibition zone diameters of each restorative materials were measured. No distinct inhibition zone was reported; only a slight zone (6 mm) around the contact surfaces of each material was observed after the 24-hour and 48-hour incubations. No significant difference was observed in the inhibition zone diameters between the two test groups and control. Within the limitations of this study, results revealed that there was no antibacterial difference among glass ionomers prepared with propolis and chlorhexidine.
Keywords: antimicrobial; glass ionomer; cement; chlorhexidine; propolis